Fixed-time artificial insemination in Churra Galega Bragançana ewes: : DARIO tip effect - Silva, Daiane Moreira; Miranda Pires Quintas, Hélder; Sampaio dos Santos, Liliana Maria; de Carvalho Neves Álvaro, Armindo; Pereira Afonso, Paulo Jorge; CorujeiraValentim, Ramiro (Revista Agrogeoambiental, 2023)
This work was carried out with the objective of studying the effect of the anti-reflux device for ovine insemination (DARIO) on the fertility rate in ewes of the native Portuguese breed Churra Galega Bragançana (CGB) artificially inseminated at fixed-time. Eighty-one ewes aged between one and five years were used. At the end of April 2021, ewes’ reproductive control was carried out, using a short progestagen treatment (five days) + equine chorionic gonadotropin (eCG). Cervical artificial insemination (AI) was performed at fixed-time (55 hours after the end of the hormonal treatment), with cooled semen. All ewes were inseminated by the same inseminator: 39 ewes with the DARIO tip on the end of the sheath and 42 without this tip. The pregnancy diagnosis was made by ultrasonography 41 days after AI. Age and body condition (BC) did not affect the ewes’ response to the applied hormonal treatment or the fertility rate. Approximately 95.1% of the ewes responded to the progestagen + eCG treatment. Forty-one days after AI, 86.4% of the ewes were pregnant. The use of the DARIO tip did not affect the fertility rate.